Analisis Value For Money untuk Mengukur Kinerja Keuangan Jatibanggi Kabupaten Tulungagung Tahun Anggaran 2022-2024 - Mutia Tsalitsa Alawia; Wiwik Mukholafatul Farida (STIE PGRI Dewantara Jombang, 2025)
The study aims to analyze, conclude, and provide solutions on Value for Money to measure financial performance in the Karangwaru Village, Tulungagung Regency, for the 2022-2024 fiscal years. This research uses descriptive quantitative methods with an applied objective, and data collection techniques include observation, documentation, and unstructured interviews. Secondary data is utilized. In terms of effectiveness, revenue realization consistently reached or exceeded the target with an average ratio of 98%, indicating a less effective performance. For the economic aspect, the same average ratio of 92.79% was achieved, which is categorized as economical. Generally, the financial performance of Karangwaru Village is considered less effective, necessitating improved accuracy in expenditure planning to prevent wastage. The Value for Money approach proved beneficial as a reference before preparing the Village Revenue and Expenditure Budget Plan (RAPBDes) for the following year.